2018
DOI: 10.1097/meg.0000000000001177
|View full text |Cite
|
Sign up to set email alerts
|

Golimumab effectiveness and safety in clinical practice for moderately active ulcerative colitis

Abstract: These real-world clinical data suggest that GLB is an effective and safe therapy for a UC cohort with significant previous anti-TNF exposure. An elevated baseline C-reactive protein, likely reflective of increased inflammatory burden, is associated with a reduced likelihood of a successful outcome of GLB therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
2
9
0
Order By: Relevance
“…The finding is also consistent with the results of the BE-SMART study, where mucosal healing at week 14 was found to be associated with continuation of steroid-free golimumab at week 52 [27]. Other previously reported predictors of treatment outcome, such as concomitant use of immunomodulators [28,36], low clinical disease activity [28,29], or previous use of anti-TNF [26,31], could not be confirmed as long-term predictive factors in our cohort.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The finding is also consistent with the results of the BE-SMART study, where mucosal healing at week 14 was found to be associated with continuation of steroid-free golimumab at week 52 [27]. Other previously reported predictors of treatment outcome, such as concomitant use of immunomodulators [28,36], low clinical disease activity [28,29], or previous use of anti-TNF [26,31], could not be confirmed as long-term predictive factors in our cohort.…”
Section: Discussionsupporting
confidence: 91%
“…In previous reports on the short-term clinical effectiveness of golimumab, the results have varied considerably depending on the study population and on the definitions of response and remission [12,13,[26][27][28][29][30][31][32]. Bosca-Watts et al reported that 70% of the patients managed at ten hospitals in the community of Valencia, Spain had a clinical response, defined as a decrease in partial Mayo Clinic score of !3 points by week 14, whereas the corresponding figure at a tertiary referral centre in Belgium was only 14% when a clinical response was defined as the absence of diarrhoea and blood [26,28].…”
Section: Discussionmentioning
confidence: 99%
“…[27] O'Connell et al reported a large retrospective real-world study evaluating effectiveness and safety of golimumab as induction and maintenance therapy for UC in six centers in Ireland. [28] Seventy-two consecutive patients were included, 64% of them were anti-TNF naïve. The clinical response rate at month 3 and the corticosteroid-free clinical remission at month 6 were 55% and 39%, respectively.…”
Section: Real World Retrospective Studiesmentioning
confidence: 99%
“…A CRP-level higher than 5 mg/l at baseline was associated with failure to achieve 6-month corticosteroid-free remission and a shorter time to golimumab discontinuation. [28] In a large retrospective nationwide cohort from Canada, Bressler et al evaluated treatment persistence of golimumab in 136 UC patients. [29] After 1 year, persistence rate of golimumab was 63%, and the median time to golimumab discontinuation was 530 days, with no significant differences between anti-TNF naïve and experienced patients (550 versus 530 days, p>0.05).…”
Section: Real World Retrospective Studiesmentioning
confidence: 99%
“…Finally, O’Connell and colleagues 16 evaluated 72 UC patients receiving golimumab in Ireland. Clinical response was measured at 3 months and corticosteroid-free remission was measured at 6 months, the rates being 55 and 39%, respectively.…”
Section: Real-world Observational Effectiveness Studiesmentioning
confidence: 99%